Gaya Kepemimpinan Kepala Distrik Heram Kota Jayapura - Kambana, Aloysius; Lefaan, Avelinus (Universitas Cenderawasih, 2023)
The importance of leadership in managing organized human groups, so the role of leaders in improving organizational performance is very significant. This article aims to describe and analyze the leadership style of the Heram District of Jayapura City. The research method is descriptive qualitative. The research site is Heram District, Jayapura City. The informants were purposively selected by determining the categories of informants, district heads and Waena district staff. Data collection techniques used were observation and interview. The data analysis techniques include stages of data reduction, data presentation, and drawing conclusions. The results of the research show that there are three characteristics of the leadership model of the Heram District Head of Jayapura City, namely first, the rational-legal leadership model, meaning leadership is achieved based on appointment from the Jayapura Municipal Government Authority based on laws and regulations, second, communicative-coordinative, meaning leadership that is open, listening and directing and protecting all the people he leads, namely employees and residents in his leadership area, and the three models of exemplary leadership, because he shows this from his work experience, rising from ordinary staff to district head. In carrying out this leadership, the participation of the employees is needed to move the organization so that when communication and coordination work well, the goals of the organization can be achieved.